2014
DOI: 10.1007/s00259-014-2893-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term tolerability of PRRT in 807 patients with neuroendocrine tumours: the value and limitations of clinical factors

Abstract: Identified risk factors provide a limited (<30 %) risk estimate even with target tissue dosimetry. These data strongly suggest the existence of unidentified individual susceptibilities to radiation-associated disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
363
4
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 394 publications
(399 citation statements)
references
References 25 publications
21
363
4
11
Order By: Relevance
“…In large trials, grade 3 or 4 hematologic toxicity has been reported in 3%-14% of the patients (26)(27)(28). Long-term myelotoxicity in the form of myelodysplastic syndrome or acute leukemia is a rare and severe adverse event associated with PRRT, occurring in 1%-2% of patients (29).…”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…In large trials, grade 3 or 4 hematologic toxicity has been reported in 3%-14% of the patients (26)(27)(28). Long-term myelotoxicity in the form of myelodysplastic syndrome or acute leukemia is a rare and severe adverse event associated with PRRT, occurring in 1%-2% of patients (29).…”
Section: Safetymentioning
confidence: 99%
“…SSAs are partially reabsorbed in the proximal tubule cells; counteracting this reabsorption with the coinfusion of positively charged amino acids during treatment results in a mean dose reduction in the kidneys of 40% (32). Severe renal toxicity has been reported in 0%-9% of patients; high incidences have been reported in some trials with 90 Y because of its biologic and physical properties and treatment in an early era without amino acid renal protection (26,27). With renal protection being the standard of care in international protocols, some radiation nephropathy is still considered normal.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…A dose in the range of 2.7-5.4 GBq is administered according to standard protocols proposed by European Association of Nuclear Medicine (EANM). In order to protect the renal function, positively charged amino acids are coadministered (lysine and arginine) [8,9]. It is known that this kind of peptide binds very quickly to tumor tissue, while the rest of the activity is excreted through the kidneys and bladder.…”
Section: Methodsmentioning
confidence: 99%
“…The first reports of these complications were in association with high-administered activities of 111 Indiethylenetriaminepentaacetic acid (DTPA)-octreotide delivered therapeutically to cumulative activities in excess of 100 GBq [26] but have also been seen in patients receiving 177 Lu [8] and 90 Y SSAs [9]. In an article recently published in the European Journal of Nuclear Medicine and Molecular Imaging, Bodei et al [27] analyse the toxicity associated with PRRT in 807 patients with NET treated at their facility. This series provides further evidence of the low side effect profile of PRRT.…”
mentioning
confidence: 99%